2006
DOI: 10.1039/b516193b
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric multiphase chemistry of 2,5- and 2,6-dimethylphenols: determination of the mass accommodation coefficients and the Henry’s law constants

Abstract: The uptake of 2,5-dimethylphenol and 2,6-dimethylphenol on aqueous surfaces was measured between 279 and 293 K, using the wetted-wall flow tube technique coupled with UV absorption spectroscopic detection. For both compounds, the uptake coefficients gamma were found to be independent of the KOH scavenger concentration in the range of 0.01 to 1 M (pH > pK(a)) and of the liquid-gas contact times. In addition, the uptake coefficients and the derived mass accommodation coefficients alpha show a negative temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…Similarly, a droplet train flow reactor measurement for phenol at 283 K yielding α = 0.027 ± 0.005 is in excellent agreement with the temperature dependent wetted wall flow reactor data of Müller and Heal that yielded values of 0.037 at 278 K and 0.012 at 288 K. Heal et al also measured α = 0.018 ± 0.005 for aniline at 283 K and reported an upper limit of 0.001 for toluene. Schütze and Herrmann used a suspended droplet flow reactor technique to measure uptake coefficients at 293 K for acetone, 2-butanone, 2,3-butanedione, and 2-oxypropanal; their modeled value of α = 0.0021 (+0.0009/-0.0008) for acetone agrees well with the temperature dependent values measured by Duan et al shown in Table .…”
Section: Trace Gas Uptake: Experimental Resultssupporting
confidence: 81%
“…Similarly, a droplet train flow reactor measurement for phenol at 283 K yielding α = 0.027 ± 0.005 is in excellent agreement with the temperature dependent wetted wall flow reactor data of Müller and Heal that yielded values of 0.037 at 278 K and 0.012 at 288 K. Heal et al also measured α = 0.018 ± 0.005 for aniline at 283 K and reported an upper limit of 0.001 for toluene. Schütze and Herrmann used a suspended droplet flow reactor technique to measure uptake coefficients at 293 K for acetone, 2-butanone, 2,3-butanedione, and 2-oxypropanal; their modeled value of α = 0.0021 (+0.0009/-0.0008) for acetone agrees well with the temperature dependent values measured by Duan et al shown in Table .…”
Section: Trace Gas Uptake: Experimental Resultssupporting
confidence: 81%
“…2,5-Xylenol is a valuable intermediate for the preparation of phenolic resins, dyes, antiseptics, etc 1 . It was originally extracted from coal tar and then synthesized by chlorination or sulfonation of p-xylene 2 .…”
Section: Introductionmentioning
confidence: 99%